A Study on Status of Empowerment of Women in Jamnagar District - Yadav , Sudha B; Vadera , Bhavin; Mangal , Abha D3; Patel , Neha A; Shah , Harsh D (National Journal of Community Medicine, 2011)
Background: Empowerment of women is important for decision making in relation to health seeking, family planning, nutrition and economic issues, for her as well as for the family. Aim: To assess the level of empowerment of women in Jamnagar district. Settings and design: A cross sectional study was designed in rural and urban areas of Jamnagar district. Material and methods: An open-ended questionnaire was used for data collection on parameters relating to women empowerment through house-to-house survey. Statistical analysis: Chi-square was used. Results: Mean age of participants was 30.74 ± 7.65 years, 14.77% were illiterate, majority of women were housewives, 28.86% were not involved in decision regarding their marriage and 14.09% were not involved in household decisions. About quarter had no say in financial matters of family and 57% didn’t hold any bank account. The condition was worse for rural and urban slum women. 21% of the women had experienced some kind of domestic violence, which was higher in case of urban women. About one fifth of the women had no role in decisions related to reproductive health viz; spacing and of number of children, methods of family planning. Conclusion: one fifth of the women had no say regarding the reproductive issues and similarly a quarter had no participation in financial decisions. One in every five (21.47%) had faced domestic violence in some form. Education, employment had a positive impact on status of women in relation to empowerment.